2023
DOI: 10.1007/s00126-023-01169-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stage metal enrichment and formation of gold mineralization in black shales: the role of high heat flow in a rift setting

Abstract: Black shales may serve as an important source of metals such as Co, Ni, or As, largely due to anoxic to euxinic conditions in association with high concentrations of sulfur leading to efficient scavenging and transport of metals from seawater into the seafloor sediment. We report on an unusual type of Au mineralization newly discovered in Ediacaran trench-slope black shales in the Bohemian Massif, Czech Republic. The Au enrichment is related to the formation of a quartz–sulfide vein system and a progressive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Prior research has shown that diagenetic pyrite acts as a host for a variety of important trace metals in black shale. [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that diagenetic pyrite acts as a host for a variety of important trace metals in black shale. [12,13].…”
Section: Introductionmentioning
confidence: 99%